A death in Door County - Ryan, Annelise (Ryan, Annelise. Monster hunter mystery, 2022)
"A Wisconsin bookstore owner and cryptozoologist is asked to investigate a series of deaths that just might be proof of a fabled lake monster in this first installment of a new mystery series by USA Today bestselling author Annelise Ryan. Morgan Carter, owner of the Odds and Ends bookstore in Door County, Wisconsin, has a hobby. When she's not tending the store, she's hunting cryptids--creatures whose existence is rumored but never proven to be real. It's a hobby that cost her parents their lives but one she'll never give up on. So when a number of bodies turn up on the shores of Lake Michigan with injuries that look like bites from a giant unknown animal, police chief Jon Flanders turns to Morgan for help. A skeptic at heart, Morgan can't turn down the opportunity to find proof of an entity whose existence she can't definitively rule out. She and her beloved rescue dog, Newt, journey to the strait known as Death's Door to hunt for a homicidal monster in the lake, but if they're not careful, she just might be its next victim"--